Dual-wavelength laser speckle technique for absolute angle sensing In two dimensions - Gibson, Samantha Jayne (Cranfield University, 2022)
This thesis presents the theory, development, and construction of a novel absolute angle sensor employing dual-wavelength laser speckle for use in measuring two dimensional surface tilt angles. The targeted application is robotic manufacturing, specifically robot drilling where perpendicularity to the workpiece is particularly important and an accuracy of up to 0.1° is desired. The proposed technique uses two collinear beams of differing wavelengths, illuminating the surface of interest. The generated speckle patterns are shifted with respect to each other, with the position and orientation of the shift being directly related to the two dimensional tilt of the surface. This relationship is derived mathematically, and a number of experimental results are presented to confirm its validity. Two full implementations of the sensor were tested and characterised. The first used a single laser outputting two longitudinal modes with a wavelength separation of 0.5nm. Initial results in one dimension presented measurements over the wide angle range of ±45.00°, with an average absolute bias error of around 0.51°. These errors were smaller at smaller magnitudes, averaging around 0.22° between ±11.2°. Further experiments in two dimensions focused on the magnitude range ±7.50°, finding average absolute bias errors of 0.15° in θx and 0.08° in θy. The estimated standard deviations in these measurements were 0.10° in θx and 0.18° in θy. The second sensor used two separate lasers with a wavelength separation of 21.5nm, increasing the sensitivity by a factor of 40. This sensor showed greater wavelength instability due to the two independent lasers and an increased mode instability. As such, the overall errors in experimental results were greater than expected, and the data were filtered to demonstrate the achievable performance if this laser instability were resolved. Results for surface tilts up to ±0.25° in two dimensions showed average absolute bias errors of 0.007° in θx and 0.009° in θy after filtering, and standard deviations of 0.003° in θx and 0.017° in θy. These results demonstrate that the dual-wavelength speckle technique has the potential to provide high accuracy absolute angle measurements in two dimensions.